PEMIDANAAN PELAKU TINDAK PIDANA DENGAN SENGAJA MEMBAWA ALAT BERAT MELAKUKAN KEGIATAN PERKEBUNAN KAWASAN HUTAN TANPA IZIN (STUDI PUTUSAN NOMOR 2499 K/Pid.Sus-LH/2019) - Filipus A.P. Meiman Dakhi (Jurnal Panah Hukum, 2025)
The criminal act of clearing plantation land in a forest area is a crime that can damage the ecosystem and damage the order of other living creatures in the forest. Decision number 2499 K/Pid.Sus-LH/2019 is one of the decisions where there was a case of carrying heavy equipment to carry out plantation activities in a forest area. Therefore, this research aims to determine and analyze the punishment of criminals who deliberately carry heavy equipment to carry out plantation activities in forest areas without permission. This research uses a type of normative legal research with the statutory regulatory approach, case approach, comparative approach, and analytical approach by collecting secondary data consisting of primary legal material, secondary legal material, and tertiary legal material. The data analysis used is descriptive qualitative data analysis, by drawing conclusions deductively. Based on the research findings and discussion, it can be concluded that the Supreme Court decision Number 2499 K/Pid.Sus-LH/2019 rejecting the perpetrator's cassation petition is correct and at the same time immediately has permanent legal force. So the criminal decision given to the perpetrator at the previous trial was considered valid, namely the Rengat District Court decision number 461/Pid.B/LH/2018/PN.Rgt. This is because the perpetrator's actions carried out activities to clear land for oil palm plantations in the Keritang River-Gansal River Production Forest Area (HPT) using heavy equipment in the form of an excavator which was carried out by the perpetrator without a Forest Area Release permit from the authorized official, namely the Minister of Forestry, so that as a result of the perpetrator's actions can damage the ecosystem in the forest area, based on this, the perpetrator is sentenced to imprisonment for 3 (three) years and 8 (eight) months and a fine of Rp. 2,000,000,000.00 (two billion rupiah) with the provision that if the fine is not paid then replaced with imprisonment for 2 (two) months. The author advises every corporation in the business sector to always carry out business by completing legal administration in accordance with applicable regulations.